1983
DOI: 10.1111/j.1749-6632.1983.tb35178.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Sensor Model of Erythrocyte Shape Control

Abstract: On the basis of recent studies a model of erythrocyte shape control is presented. This model is based on the assumption that the erythrocyte shape is normally determined by relative surface tensions of the two membrane bilayer surfaces. Our studies have indicated that the erythrocyte shape is preserved and can be restored upon perturbation by an active process. Consequently, it is proposed that in the "bilayer sensor" model the cells "sense" changes in the relative surface tensions, activating a process that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The deviations from the normal erythrocyte shape (discocyte) are described using nomenclature according to Bessis . All isopimaranes caused formation of echinocytic forms, suggesting their incorporation into the outer leaflet of the erythrocyte membrane. The labdanes 1 − 4 and 11 caused formation of stomatocytes, indicative of incorporation into the inner membrane leaflet. The extent of membrane modifications increased with concentration (Table ) and correlated well with the concentrations at which P. falciparum growth inhibition was observed (Table ). Compound 7 , showing the lowest IC 50 value, caused progressive transformation of discocytes toward echinocytes starting at the lowest concentrations.…”
Section: Resultsmentioning
confidence: 93%
“…The deviations from the normal erythrocyte shape (discocyte) are described using nomenclature according to Bessis . All isopimaranes caused formation of echinocytic forms, suggesting their incorporation into the outer leaflet of the erythrocyte membrane. The labdanes 1 − 4 and 11 caused formation of stomatocytes, indicative of incorporation into the inner membrane leaflet. The extent of membrane modifications increased with concentration (Table ) and correlated well with the concentrations at which P. falciparum growth inhibition was observed (Table ). Compound 7 , showing the lowest IC 50 value, caused progressive transformation of discocytes toward echinocytes starting at the lowest concentrations.…”
Section: Resultsmentioning
confidence: 93%
“…Thus, compounds 1, 4 and 6 having a functional group at C-28 that is capable of acting as a hydrogen bond donor (COOH, CONH 2 , CH 2 OH) are echinocytogenic, while the presence at this position of a group that cannot donate a hydrogen bond (CH 3 , CHO, COOCH 3 ) results in stomatocytogenic compounds 2, 3 and 5 ( Table 2). According to the classical bilayer couple theory, 5,47,48 echinocytes are formed when a compound incorporates into and expands the outer leaflet of the membrane lipid bilayer, whereas stomatocytes are formed when the incorporation takes place predominantly into the inner leaflet. Thus, 1, 4 and 6 are apparently incorporated mainly into the outer leaflet, and 2, 3 and 5 into the inner leaflet.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that amphiphiles causing transformation of erythrocytes into stomatocyte forms generally behave as apparent, moderately potent antiplasmodial agents in vitro [15]. Stomatocytes are produced when amphiphiles present at sublytic concentrations incorporate into the erythrocyte membrane and cause expansion of the inner membrane leaflet [16]. The changes of the erythrocyte membrane at concentrations around IC 50 values could be observed in detail by electron microscopy [15].…”
Section: Lettermentioning
confidence: 99%